2022
DOI: 10.3389/fmed.2022.796809
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Impulse Oscillometry in Evaluating Disease Severity and Predicting the Airway Reversibility in Patients With Bronchiectasis

Abstract: BackgroundImpulse oscillometry (IOS) can be used to evaluate airway impedance in patients with obstructive airway diseases. Previous studies have demonstrated that IOS parameters differ between patients with bronchiectasis and healthy controls. This study aims to explore the usefulness of IOS in assessing disease severity and airway reversibility in patients with bronchiectasis.MethodSeventy-four patients with non-cystic fibrosis bronchiectasis who visited our Respiratory Medicine outpatient clinic were consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In addition, the reactance indices X5 and Fres significantly increase in moderate to severe asthma patients compared to those with mild disease. It is because the Fres is a sensitive indicator to airway obstruction, at which point the forces of inertia and capacitance are equal [ 10 , 33 ]. Likewise, the reactance indices X5 reflect the physical properties of the lung parenchyma and its ability to expand and facilitate alveolar filling in peripheral airways [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the reactance indices X5 and Fres significantly increase in moderate to severe asthma patients compared to those with mild disease. It is because the Fres is a sensitive indicator to airway obstruction, at which point the forces of inertia and capacitance are equal [ 10 , 33 ]. Likewise, the reactance indices X5 reflect the physical properties of the lung parenchyma and its ability to expand and facilitate alveolar filling in peripheral airways [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Combined with traditional spirometry, IOS may increase the clinical recognition of some airway diseases in the early stage. In fact, we have proved the usefulness of IOS in evaluating and predicting disease severity in bronchiectasis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detection of changes in the bronchi and reduced lung elasticity observed in bronchiectasis renders IOS a suitable tool for assessing its severity. Several previous studies have explored IOS parameters in assessing bronchiectasis severity, with some highlighting correlations between resonance frequency (Fres) and FACED scores [24], whereas others noted associations between FACED scores and peripheral resistance than X5 or Fres [25]. Despite these promising ndings, uncertainties remain, warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on patients with non-PCD bronchiectasis have reported a strong correlation between FOT parameters and the severity of bronchiectasis disease [ 25 ]. Another study highlighted that total breath reactance at 5 Hz (X 5 ) could effectively differentiate between healthy subjects and patients with obstructive pulmonary diseases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of Tan C. et al, bronchiectasis severity scores exhibited positive correlations with various FOT parameters, including R 5 , R 5 -R 20 , resonance frequency, airway impedance at 5 Hz, peripheral resistance, and negative correlation with X 5 [ 25 ]. In our study, we utilized the multi-frequency mode of FOT to measure pulmonary resistance and reactance at frequencies 5-11-19 Hz.…”
Section: Discussionmentioning
confidence: 99%